2023
DOI: 10.7759/cureus.35951
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Arthritis Associated with COVID-19 Vaccination

Abstract: COVID-19 vaccines have been shown to be highly efficacious in preventing symptomatic COVID-19 infections throughout the pandemic. There have been emerging cases of inflammatory arthritis occurring in close relation to COVID-19 vaccination. We illustrate a case of new-onset inflammatory arthritis 10 days after receiving their second Vaxzevria COVID-19 vaccine. The patient responded dramatically to prednisolone treatment but subsequently required hydroxychloroquine due to persistent inflammatory joint symptoms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Among the patients with rheumatoid arthritis (RA), twelve [8,11,101,113,115,139,140,191] were seronegative, and nine [69,101,129,133,164,191,192] were seropositive for anti-cyclic citrullinated peptide (CCP) antibodies or rheumatoid factor (RF) or both. Among these, six patients [69,101,129,164,193] had both RF and CCP positives, and three patients [101,133,191] were only positive for RF.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
See 2 more Smart Citations
“…Among the patients with rheumatoid arthritis (RA), twelve [8,11,101,113,115,139,140,191] were seronegative, and nine [69,101,129,133,164,191,192] were seropositive for anti-cyclic citrullinated peptide (CCP) antibodies or rheumatoid factor (RF) or both. Among these, six patients [69,101,129,164,193] had both RF and CCP positives, and three patients [101,133,191] were only positive for RF.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Among these, six patients [69,101,129,164,193] had both RF and CCP positives, and three patients [101,133,191] were only positive for RF. The majority (seventeen patients, 80%) had polyarthritis presentation [8,11,101,113,115,129,164,191,192], whereas two had oligoarthritis [69,133] and another two had monoarthritis presentation [139,140]. A total of eighteen patients received corticosteroids, eleven patients received disease-modifying antirheumatic drugs (DMARDs), six received methotrexate [69,101,133,164,192], two received leflunomide [101,191], one received mycophenolate [11], three received HCQ [113,164,192], one received sulphasalazine [164], and four patients received biologic drugs: tocilizumab for one [133], etanercept for one [115], adalimumab for one [101], and golimumab for one patient [101].…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the possibility of late COVID-19 manifestation, it has been shown that vaccination might trigger some related symptoms. The majority of vaccine inflammatory arthritis onset occur up to seven days post administration, however, they can occur later as well [ 18 ].…”
Section: Discussionmentioning
confidence: 99%